Comparing the contents of outcome measures in upper-limb amputation using the International Classification of Functioning, Disability, and Health: A systematic review - Hatice Gül; Senem Demirdel; Tezel Yıldırım Şahan; Bahar Anaforoğlu Külünkoğlu; Sevilay Seda Baş; Senay Çerezci Duygu; Murat Ali Çınar; Hilal Keklicek; Kezban Bayramlar; Fatih Erbahçeci; Çınar, Murat Ali (My University, 2024)
The International Classification of Functioning, Disability, and Health (ICF) provides a universal framework for assessing the functioning of any person. To facilitate the application of the ICF in practice, ICF core sets are being developed. This study is part of a project intended to develop an ICF core set for upper-limb amputation (ULA) and aims to identify relevant concepts included in the outcome measurements used in studies of ULA. Articles involving ULA aged 18 years or older from January 2011 to December 2021 were searched on Cumulative Index to Nursing and Allied Health Literature, SPORTdiscus, and Medical Literature Analysis and Retrieval System Online. We included studies with particular designs (randomized controlled trials, before/after studies, cross-sectional studies, and longitudinal observational studies) and published in English. Relevant concepts were extracted from measurements and linked to the ICF using linking rules, and a frequency analysis was conducted. Sixty-one of the 1272 identified publications were included, from which 86 measurements were extracted. Concepts extracted from measurements were linked to 129 ICF categories. Three hundred twenty-six (29.23%) of the 1115 concepts were related to body functions, 643 (57.66%) to activity and participation, 96 (8.60%) to environmental factors, 19 (1.70%) to body structures, and 6 (0.53%) to personal factors. Twenty-five (2.24%) were characterized as "nd-not definable." "Fifty-four" categories identified in at least 5% of the publications will be considered for inclusion in the final ICF core set for ULA during the consensus conference. This review provides information about the content of measures, and the identified ICF categories reveal the research perspective for developing an ICF core set for ULA.